The Optimal Integration of Photovoltaic (PV) and Battery Energy Storage Systems in Power Distribution Using Hybrid Flower Pollination and β-Hill Climbing - ramadan, m.sahrul; Ihlas, Ihlas; Assalam, Imam Faried; Asri, Andarini; Arief, Ardiaty; Nappu, Muhammad Bachtiar (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
This study discusses the optimization of the placement and capacity of Photovoltaic (PV) and Battery Energy Storage System (BESS) units in the IEEE 33-bus distribution system using the Hybrid Flower Pollination Algorithm (FPA) and β-Hill Climbing (βHC) or HyFPAβHC methods. The primary objective of this research is to enhance the performance of the distribution system by reducing power losses and improving the voltage profile. Based on the optimization results, three PV units with capacities of 749.3 kW, 577.5 kW and 620 kW were optimally placed at buses 8, 13 and 20, respectively, while one BESS unit with a capacity of 1112.4 kW was installed at bus 24. Simulation results indicate that the integration of PV and BESS significantly reduces the total system power losses from approximately 50 kW on several main feeders under the base condition (without Distributed Generation) to below 5 kW after optimization. In addition, the voltage profile improved from a minimum value of 0.92 p.u. to a stable range of 0.98–1.0 p.u. Furthermore, the integration of PV and BESS contributes to mitigating power fluctuations, enhancing energy efficiency, and improving the reliability of the distribution system operation. Therefore, the HyFPAβHC method is proven to be effective in determining the optimal configuration of PV and BESS units to improve the technical performance of electrical distribution systems.